The impact of in vivo Calmette-Guerin Bacillus administration on in vitro IgE secretion in atopic children - (:unkn) unknown (MARCEL DEKKER INC, 2002)
To investigate whether a preexisting T helper (T-H) 2 type immune response could be suppressed by Calmette-Guerin Bacillus (BCG) immunization in atopic children with asthma, we determined interferon (IFN)-gamma interleukin (IL)-2, IL-4, and IL-5 and total IgE level in the supernatant of peripheral blood mononuclear cells (PBMC) of six atopic and five nonatopic children in response to phytohemagglutinin A (PHA), purified protein derivate (PPD), and Dermatophagoides pteronyssinus II allergen (Der p 11) both before and after BCG vaccination. IL-5 level in response to Der p II was significantly higher ill the atopic group than in the nonatopic group both before and after BCG vaccination (p = 0.004, p = 0.009, respectively). In the atopic group, IgE levels determined in PPD and Der p II stimulated and unstimulated culture supernatants decreased significantly after BCG vaccination (p=0.028, p=0.026, p=0.046, respectively), whereas in the nonatopic group (p = 0.041) BCG vaccination resulted in a significant decrease in IgE level only in response to Der p 11 stimulation. We concluded that in vivo BCG administration can downregulate both spontaneous and stimulated in vitro IgE secretion from PBMC of atopic children.
Keywords: atopy; BCG; children; IgE; IFN-gamma; IL-2; IL-5; THI-type immune response; KILLED MYCOBACTERIUM-BOVIS; SENSITIZED NEWBORN MICE; OVALBUMIN; INTERLEUKIN-12; INFECTION; VACCAE